ANALISIS PEMANFAATAN MEDIA INTERAKTIF SEBAGAI SARANA PENGAJARAN AL-QUR'AN DI SEKOLAH DASAR SAENGSATTHA, THAILAND - Putri Agil; Hasrian Rudi Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the use of interactive media as a means of teaching the Qur'an at Saengsattha Elementary School, Thailand, using a descriptive qualitative approach through field studies. The research subjects included students aged 6–12 years and ustaz/ustazah as the main informants. Data were collected through direct observation of the learning process, in-depth interviews, and documentation of photos, videos, and activity notes, then analyzed using the Miles and Huberman model with stages of reduction, presentation, and conclusion drawing. The results showed that the children's interest and enthusiasm for learning were very high, as reflected in their punctual attendance, active participation, and expressions of happiness and curiosity. Interactive media proved to be effective in increasing motivation and interest in reading the Qur'an, creating a fun learning atmosphere suitable for early childhood development. This study provides deep insights into the potential of interactive media in Islamic religious education in elementary schools.